New Media and Indigenous Languages as Mechanisms for Attaining Improved Political Participation and National Development - Ifeyinwa Chukwuokoro PhD; Blessing Anozie-Ibebunjo; Ekwe Ngene (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Various mechanisms can be leveraged to increase political participation among citizens of any nation. This study explores how new media and indigenous languages can be leveraged for improved political participation and national development. It is anchored on Indigenous Existential Phenomenology Theory, which calls for preservation and promotion of indigenous systems. Its objectives include determining the extent to which the two mechanisms can foster improved political participation and national development; ascertain the challenges to leveraging them; and proffer possible solutions to the challenges to the realization of the targeted goals. Exploratory survey design and mixed-methods were employed. The primary data were gathered from 300 online questionnaire respondents. The analytical tools employed include percentage, tables, interpretive devices, and content and thematic analyses. The results show that leveraging new media and indigenous in combination can pragmatically lead to improved political participation and national development. They have the capacity to improve political participation and national development, bringing to place significant changes and innovations. They can foster improved political participation and national development at very high extent. Policy lapses, attitudinal factors, digital gap, misinformation and other core challenges to leveraging the two mechanisms are ascertained. Conversely, the solutions are proffered. The study concludes that significant improved political participation and national development can be attained at a significant extent, if new media and indigenous languages are duly leveraged and the constraining challenges addressed. Stakeholders should imbibe the identified solutions for lasting solutions to the challenges, and the attainment of improved political participation.